Cardiac Patient Remote Health Monitoring (CP-RHM) using Digital Monitoring - Waghmare, Kiran; Acodkar, Anuj; Gavali, Rohit; Tiwari, Rahul; Pavnoji, Prathamesh; Naik, Sidharth (International Journal of Computer Sciences and Engineering, 2025)
Digital health is an application of digital and innovative technologies in health industry. It is a multi-disciplinary domain which involves Scientists, Researchers, Doctors and Technicians. Therefore, a new smart platform used by the Digital health is Internet of Things (IoT). An open, standards based framework enables innovators to create new ideas for e-healthcare. IoT allows innovators to design accessible, robust, affordable and secure healthcare i.e., Patient Remote Monitoring Systems which is used by Doctors, or Healthcare Practitioners to improve clinical care, research and public health. The main objective of this paper is to design remotely operated Patient Monitoring System for Cardiac patient at affordable cost.